Comparison of Polypropylene (Prolene) Versus Polydioxanone(Pds) In Abdominal Wall Closure After Laparotomy - Rai, Lajpat; Masood, Umair; Naqi, Ali; Alam, Rutaba; ., Attaullah; Liaqat, Fahim (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare polypropylene (non-absorbable) versus polydioxanone (delayed absorbable) suture for abdominal wound closure after laparotomyStudy Design: Quasi-experimental study       Place and Duration of Study: Department of General Surgery Combined Military Hospital Quetta, Pakistan from May 2020 to June 2021.Methodology:  Total 140 patients (70 each Group) of elective laparotomy who met the inclusion criteria were included. Patients with complications, previous surgery or emergency surgery were excluded. In Group A mass closure of anterior abdominal wall was done with polypropylene while in Group B mass closure was done with polydioxanone. All patients were followed for six months post operatively for complications.Results: Total 140 patients were included in the study. The mean age in Group A was 44.57±12.87 years and in Group B it was 48.47±11.45 years. There were 75(53.5%) males and 65(46.5%) females. Post operatively 29 patients (41.4%) in Group A and 20 patients (28.5%) in Group B developed surgical site infection. 10 patients (14.2%) of Group A and 8 patients (11.4%) of Group B developed incisional hernia. In Group A 5 patients (7.14%) had burst abdomen postoperatively while in Group B, 4 patients (5.71%) had burst abdomen.Conclusion: We conclude that PDS (with antibacterial coating) has reduced inflammatory reaction and has better tissue regeneration. PDS is better as it has low surgical site infection, low wound dehiscence and incisional hernia formation when compared with prolene.